Transcriptome Analysis Reveals Mechanisms by Which Lactococcus lactis Acquires Nisin Resistance - Kramer, Naomi E. (American Society for Microbiology, 2006)
Nisin, a posttranslationally modified antimicrobial peptide produced by Lactococcus lactis, is widely used as a food preservative. Yet, the mechanisms leading to the development of nisin resistance in bacteria are poorly understood. We used whole-genome DNA microarrays of L. lactis IL1403 to identify the factors underlying acquired nisin resistance mechanisms. The transcriptomes of L. lactis IL1403 and L. lactis IL1403 Nis(r), which reached a 75-fold higher nisin resistance level, were compared. Differential expression was observed in genes encoding proteins that are involved in cell wall biosynthesis, energy metabolism, fatty acid and phospholipid metabolism, regulatory functions, and metal and/or peptide transport and binding. These results were further substantiated by showing that several knockout and overexpression mutants of these genes had strongly altered nisin resistance levels and that some knockout strains could no longer become resistant to the same level of nisin as that of the wild-type strain. The acquired nisin resistance mechanism in L. lactis is complex, involving various different mechanisms. The four major mechanisms are (i) preventing nisin from reaching the cytoplasmic membrane, (ii) reducing the acidity of the extracellular medium, thereby stimulating the binding of nisin to the cell wall, (iii) preventing the insertion of nisin into the membrane, and (iv) possibly transporting nisin across the membrane or extruding nisin out of the membrane.